(3QSGdI aj GdTghQs
(3ChdgG (B:s
(3hHYO agPg OGFQI eTJedI Ydi PcQ TghQ GdYGe GdYLejI hCSeGFgG HGdSQjGfjI hGdfHWjI s
(3BNQgG (B:s
(3hEf cGf GdXdGd eG jOd Ydi CNU GdEaJbGQ eQJ ai GdCVdGY hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs